Distributed systems and numeric calculation - ISBĂŞOIU, Eliza Consuela; PREOTESESCU, Mădălin Gabriel; CHIRU, Claudiu (Annals of Spiru Haret University. Economic Series, 2010)
Many software applications are considered as being failures, due to the fact that they cannot deal with certain issues. Thus the application and the investment are not justified. This situation is named implementation trap [1]. The resolution of a false problem can damage the whole project: it can be abandoned, so one can lose time and money. The architecture offers different but complementary points of view over the soft.